Eosinophilic Granulomatosis With Polyangiitis Presenting With Oral Granuloma as the Initial Symptom: A Case Report - Lin, Lirong; Yu, Rongjie; Zheng, Luquan; Gong, Shuyu; Yang, Jurong (Frontiers in Medicine, 2022)
Antineutrophil cytoplasmic antibody associated vasculitis includes granulomatosis with polyangiitis, eosinophilic granulomatosis with polyangiitis (EGPA), and microscopic polyangiitis. While EGPA has no specific symptoms, it usually presents as necrotizing vasculitis, eosinophil infiltration of the tissues and organs, and extravascular granuloma formation. Here, we report a patient who had a rare initial presentation of oral granuloma and had been previously misdiagnosed several times at other hospitals. He was finally diagnosed with EGPA and recovered after methylprednisolone and cyclophosphamide treatment. The disease EGPA can present with a rare initial presentation of oral granuloma, methylprednisolone, and cyclophosphamide can be a suitable choice of treatment.